GROWTH PERFORMANCE OF WHITELEG SHRIMP (Litopenaeus vannamei) AT DIFFERENT STOCKING DENSITIES IN A POLYCULTURE SYSTEM WITH SEA GRAPE (Caulerpa sp.) - Valentine, Riris Yuli; Hariyadi, Dimas Rizky; Tangguda, Sartika (Politeknik Kelautan dan Perikanan Jembrana, 2025)
This study evaluated the growth performance, survival rate, and water quality improvement in a polyculture system integrating whiteleg shrimp (Litopenaeus vannamei) and sea grapes (Caulerpa sp.) with different shrimp stocking densities. This study employed a completely randomized design with three treatments, each at three levels of shrimp densities (15, 30, and 45 individuals per tank with a capacity of 0.06 m³), integrated with sea grape (50 g) for 60 days. During maintenance, shrimp were fed commercial feed, and no water changes were performed. The results showed that the highest shrimp growth and survival were obtained at a density of 15 individuals per tank, with growth rates of 6.54% day-1 and survival rates of 98% for the shrimp, resulting in optimal growth in Caulerpa sp. In contrast, a higher stocking density (45 individuals per tank) was associated with lower observed growth and survival rate of whiteleg shrimp throughout the culture period. Water quality showed favourable conditions for both, with pH levels (6.5–9.4), dissolved oxygen concentrations (5.0–8.2 mg L-1), and temperatures (26–38°C) within the optimal range. The polyculture system facilitated nutrient recycling, where shrimp waste was utilized by Caulerpa sp., effectively reducing nitrate and phosphate concentrations and preventing eutrophication in all treatments with increased stocking density. The conclusion of this study highlighted the potential of the polyculture system to improve ecological balance and productivity in aquaculture. Lower shrimp stocking densities resulted in high growth and survival, while integrating Caulerpa sp. contributed to environmental sustainability. Penelitian ini mengevaluasi performa pertumbuhan, tingkat kelangsungan hidup, dan perbaikan kualitas air dalam sistem polikultur yang mengintegrasikan udang vaname (Litopenaeus vannamei) dan anggur laut (Caulerpa sp.) dengan kepadatan tebar udang yang berbeda. Penelitian ini menggunakan rancangan acak lengkap dengan tiga perlakuan, yaitu tiga tingkat kepadatan udang (15, 30, dan 45 ekor per wadah berkapasitas 0,06 m³), masing-masing diintegrasikan dengan anggur laut (50 g) selama 60 hari. Selama pemeliharaan, udang diberi pakan komersial dan tidak dilakukan pergantian air. Hasil penelitian menunjukkan bahwa pertumbuhan dan kelangsungan hidup udang tertinggi diperoleh pada kepadatan 15 ekor per wadah, masing-masing sebesar 6,54% per hari dan 98%, serta menghasilkan pertumbuhan Caulerpa sp. yang optimal. Sebaliknya, kepadatan tebar yang lebih tinggi (45 ekor per wadah) menghasilkan pertumbuhan dan tingkat kelangsungan hidup udang vaname yang lebih rendah selama masa pemeliharaan. Kualitas air menunjukkan kondisi yang mendukung untuk keduanya, dengan pH (6,5–9,4), oksigen terlarut (5,0–8,2 mg L-1), dan suhu (26–38°C) berada dalam kisaran optimal. Sistem polikultur ini memfasilitasi daur ulang nutrien, di mana limbah udang dimanfaatkan oleh Caulerpa sp., secara efektif mengurangi konsentrasi nitrat dan fosfat serta mencegah eutrofikasi pada semua perlakuan, bahkan dengan peningkatan kepadatan tebar. Kesimpulan dari penelitian ini menyoroti potensi sistem polikultur dalam meningkatkan keseimbangan ekologis dan produktivitas di bidang akuakultur. Kepadatan tebar udang yang rendah menghasilkan pertumbuhan dan kelangsungan hidup yang tinggi, sementara integrasi dengan Caulerpa sp. berkontribusi terhadap keberlanjutan lingkungan.